2017
DOI: 10.1071/cp17156
|View full text |Cite
|
Sign up to set email alerts
|

Elevated field atmospheric CO2 concentrations affect the characteristics of winter wheat (cv. Bologna) grains

Abstract: Abstract. The aim of this study was to investigate the impact of elevated concentration of carbon dioxide (CO 2 ), as expected over coming decades, on yield and quality of winter bread wheat (Triticum aestivum L.). Plants (cv. Bologna) were grown by using the free-air CO 2 enrichment (FACE) system at Fiorenzuola d'Arda under ambient (control) and elevated (570 ppm, e[CO 2 ]) CO 2 concentrations for two growing seasons. We addressed whether there would be a response of wheat grains to elevated CO 2 concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 66 publications
(84 reference statements)
0
13
0
Order By: Relevance
“…In this case, it has been suggested that this effect did not come from deficient N remobilization in leaves but rather a N dilution effect, whereby the quantity (or size) of grains increased while the total available N for remobilization did not change. In addition, under FACE conditions, an increase in the glutenin-to-gliadin ratio has been found ( Pandey et al , 2017 ), as well as a general decrease in all storage proteins except for globulins and albumins ( Wieser et al , 2008 , but see Verrillo et al , 2017 , where globulins also decreased). Metabolic analyses have demonstrated that at elevated CO 2 , grains contain more secondary metabolites (shikimate and quinate) and free hexoses (fructose and glucose) but less sucrose and alanine, regardless of developmental stage.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, it has been suggested that this effect did not come from deficient N remobilization in leaves but rather a N dilution effect, whereby the quantity (or size) of grains increased while the total available N for remobilization did not change. In addition, under FACE conditions, an increase in the glutenin-to-gliadin ratio has been found ( Pandey et al , 2017 ), as well as a general decrease in all storage proteins except for globulins and albumins ( Wieser et al , 2008 , but see Verrillo et al , 2017 , where globulins also decreased). Metabolic analyses have demonstrated that at elevated CO 2 , grains contain more secondary metabolites (shikimate and quinate) and free hexoses (fructose and glucose) but less sucrose and alanine, regardless of developmental stage.…”
Section: Introductionmentioning
confidence: 99%
“…Four dishes were allocated for each treatment (C, M and S). Fifty seed were placed in each dish, and incubated in the dark at room temperature for 7 days (40). The dishes were monitored and 2 mL water were added regularly.…”
Section: Physical Soil Propertiesmentioning
confidence: 99%
“…The shoot and root dry weight of wheat varieties were increased by an average of 17% and 36%, respectively, at high CO 2 concentration [4]. Both the stem elongation and leaf area index were also increased by 21%, which resulted in a 26% increase in grain yield [5]. The length, leaf area and dry weight of yams were also significantly increased in elevated CO 2 [6].…”
Section: Introductionmentioning
confidence: 96%